Online Implementation Of Imc Based Pid Controller In Batch Esterification Reactor. - Zulkeflee, S.A.; Shaari, N.; Aziz, N. (2010)
Esterification is one of important process that operates in a batch reactor. Since the inherent nonlinear properties of this batch reactor, the control of such reactor to ensure an efficient operation remains a great challenge.